Non-invasive detection of fractures, fracture zones, and rock damage in a hard rock excavation - Experience from the Aespo Hard Rock Laboratory in Sweden - Walton, G; Lato, M; Anschuetz, H; Perras, MA; Diederichs, MS (Engineering geology, 2015)
A key requirement for licensing of the construction of underground repositories for nuclear waste is the demonstrated capability to verify design assumptions involving the presence and extent of the excavation damage zone around tunnels, shafts, emplacement holes and caverns. As part of ongoing work to select and refine key technologies and techniques towards this end, geophysical surveys were performed at two locations within the Aespo Hard Rock Laboratory in Sweden. Earth resistivity (RES), induced polarization (IP), and Ground Penetrating Radar (GPR) data were collected using a variety of survey parameters; Light Detection and Ranging (LiDAR) data were collected as a reference for surface structures, surface topography, and site geology. Based on an analysis of the data, models for the Highly Damaged Zone (HDZ) and Excavation Damage Zone (EDZ) at both sites were developed. The HDZ was found to be approximately 5 to 10cm in thickness, and the EDZ was found to extend between 15 and 35cm below the excavation surface. Two-dimensional (2D) RES profiling generated the most reliable assessment of the HDZ, whereas chargeability data and GPR data were more useful in the estimation of the EDZ dimensions.